Chronic deficit in nitric oxide elicits oxidative stress and augments T-type calcium-channel contribution to vascular tone of rodent arteries and arterioles - Howitt, Lauren; Kuo, Ivana Y.; Ellis, Anthie; Chaston, Daniel J.; Shin, Hee-Sup; Hansen, Pernille B.; Hill, Caryl E. (OXFORD UNIV PRESS, 2013)
As cardiovascular disease is characterized by reduced nitric oxide bioavailability, our aim was to determine the impact of this change on the mechanism underlying vascular tone of pressurized arteries in vitro and in vivo. We used pressurized cerebral and mesenteric arteries in vitro and skeletal muscle arterioles in vivo to study the contribution of L-type (1 mol/L nifedipine) and T-type (1 mol/L mibefradil, 3 mol/L NNC 550396) calcium channels to vascular tone, following acute or chronic inhibition of nitric oxide. Acute inhibition with l-NAME (10 mol/L) significantly increased the T-type, but not the L-type, channel contribution to vascular tone in vitro and in vivo, and altered the smooth muscle expression of the Ca(v)3.1 and Ca(v)3.2 T-type channels. In pressurized mesenteric arteries of Ca(v)3.1ko and Ca(v)3.2ko mice, acutely treated with l-NAME, the contribution of T-type channels relative to L-type channels was significantly reduced, compared with arteries from wild-type mice.Chronic l-NAME treatment (40 mg/kg/day; 1418 days) increased blood pressure, vascular superoxide, and the contribution of T-type channels to vascular tone in vivo. The latter was reversed by acute scavenging of superoxide with tempol (1 mmol/L), or inhibition of NADPH oxidase with apocynin (500 mol/L) or DPI (5 mol/L). We conclude that nitric oxide deficit produces a significant increase in the contribution of Ca(v)3.1 and Ca(v)3.2 T-type calcium channels to vascular tone, by regulating the bioavailability of reactive oxygen species produced by NADPH oxidase. Our data provide evidence for a novel causal link between nitric oxide deficit, oxidative stress, and T-type calcium channel function.